The faithful triangular representations of Kaloujnine $p$-groups over a $p$-element field - Leonov, Y.G. (Carpathian Mathematical Publications, 2011)
The faithful triangular representations of finite Kaloujnine $p$-groups is studied. Images of generators of those groups are described. Infinite-dimensional representation of the direct limit of Kaloujnine $p$-groups is regarded.